Otherwise than literal: convergence and the unworking of allegory in Tsitsi Dangarembga's Tambudzai trilogy. Issue 12 (1st December 2020) - Griffiths, Michael R.
ABSTRACT: How does the form of the Bildungsroman reflect the drive to decolonisation? If the world or postcolonial Bildungsroman is concerned with figuring the development of human personality (as Joseph Slaughter has argued), it is at one and the same time concerned with the allegorisation of national development. Yet, the political exigencies that urge on the writing of decolonisation can equally be served by realism. Perhaps the paradigmatic postcolonial Bildungsroman, Tsitsi Dangarembga's Nervous Conditions is also notable for the tension it presents between realism and allegory. This article makes an intervention in the politics of such formalist debates within the Bildungsroman as the tension between allegory and realism or the temporality of its narration in order to gauge their relation to decolonisation. In so doing, it examines Dangarembga's Tambudzai trilogy—including the two sequels The Book of Not and This Mournable Body —and its intertexts, such as the work of Frantz Fanon.